A Case Report and Literature Review of Mesalazine-Induced Kidney Injury in a Pediatric Patient With Ulcerative Colitis - Wang, Shuo; Zhou, Pengxiang; Li, Zailing (Frontiers in Pediatrics, 2022)
Background Mesalazine, a preparation of 5-aminosalicylic acid, is a medication widely used in clinical practice as a first-line therapy in the treatment of mild and moderate inflammatory bowel disease. However, mesalazine has nephrotoxicity and can cause adverse events in the renal system. While these adverse reactions are very rare, they may have serious consequences. Case presentation The patient was a 14-year-old boy who had a 5-year history of ulcerative colitis (UC). He received mesalazine due to relapse. Abnormal urinalysis results and urinary protein content were observed 2 months after the initiation of the mesalazine treatment, antibiotic treatment failed, and the urine analysis returned to normal after discontinuation of mesalazine. However, the patients renal function worsened again after restarting mesalazine therapy. Ten cases of mesalazine-induced renal injury were identified using a systematic literature review. We found that: 1) mesalazine-induced renal injury was more common in boys with UC; 2) all cases had proteinuria or leukocyturia; 3) renal injury might progress to end-stage renal disease; and 4) timely withdrawal of the drug and steroid therapy might contribute to improved renal function. Conclusion Urinalysis results and renal function should be monitored regularly in pediatric patients receiving mesalazine therapy to avoid renal insufficiency and renal failure.